Answer:
The result for this equation is [tex]x = -5[/tex] .
Step-by-step explanation:
-Solve the equation:
[tex]3(4x-10)=2(3x-30)[/tex]
-Use Distributive Property:
[tex]3(4x-10)=2(3x-30)[/tex]
[tex]12x - 30=6x - 60[/tex]
-Subtract 6x and from 12x :
[tex]12x - 30 -6x=6x -6x - 60[/tex]
[tex]6x - 30=-60[/tex]
-Add both sides by 30:
[tex]6x - 30 +30=-60 +30[/tex]
[tex]6x =-30[/tex]
-Then, you divide both sides by 6:
[tex]\frac{6x}{6}=\frac{-30}{6}[/tex]
[tex]x = -5[/tex]
So, therefore the answer is [tex]x = -5[/tex] .